Tap stand sullage disposal via irrigation pipes - Rod Shaw (1258020) (2024)
Sanitation in humanitarian settings from: Sanitation in Humanitarian Settings R.A Reed Published by  Practical Action Publishing In an emergency the collection, treatment and disposal/reuse of human waste is critical to the health, wellbeing and environment of affected populations. Addressing this is difficult and complex requiring an understanding of the technical, social, institutional, political and environmental issues affecting the situation. In large emergencies where international relief agencies are involved there usually will be specialists available to advise and assist inexperienced field staff deliver essential services. However, most emergencies are not large. They are local in nature and rely on local officials to provide an emergency response, especially in the early stages of the emergency. It is very likely that these officials will have minimal knowledge and experience of emergency response, indeed they have probably never been faced with such an event before. This book sets out to assist such individuals. Working from a technical perspective, it provides an understanding of the critical elements controlling the delivery of human waste related services, together with strategies for decision making and guidance on how to design, construct and operate key infrastructure. The book concentrates on the acute response and stabilization phases of an emergency – but much of the content is equally relevant to the long term and rehabilitation phases. Donate and support this book project and we will send copies of this book to communities in need of this important guide. Published: 2024 Pages: 392 eBook: 9781788532679 Paperback: 9781788532655 Hardback: 9781788532662